The Journey to MaaS - Friis, Gustav; Dzubur, Ajla (Proceedings from the Annual Transport Conference at Aalborg University, 2018)
Through a pilot project of a real solution for Mobility as a Service (MaaS), municipalities in Business Region Aarhus want to investigate the possibility for creating a more efficient mobility system by integrating public and private mobility services. This calls for a setup that includes both mobility providers, data platform owners, service providers and the travellers. The project demonstrates a new way of organising the mobility system in the region. The demonstration project will combine public transport solutions with private peer-to-peer ridesharing in an integrated solution in a real-life environment. The mobility solution will be based on the principles of MaaS. The main goal of the project is to demonstrate a new way of organising mobility on the foundation of a sound and sustainable business case.